Adoção da tecnologia da informação em organizações rurais: O caso da pecuária de corte - De Camargo Ferraz MacHado, João Guilherme [UNESP]; Nantes, José Flávio Diniz (FapUNIFESP (SciELO), 2011)
Adoption of technology. Farm management. Beef cattle breeding. Information technology.This research is aimed to study the use and the diffusion of IT in the beef cattle breeding from the analysis of the factors that have influenced its adoption as well as to describe resources, procedures, and necessary actions for IT operation using case studies in rural properties classified by the innovativeness degree. This study was carried out in two stages, quantitative and qualitative. In the first stage, a survey with producers was conducted. Information concerning the different technologies adopted enabled to identify the level of innovativeness of those producers. They were classified according to the similarities of the technological position. The second stage analyzed experiences, opinions, and perspectives regarding the technology integrated to the productive system. Two rural cattle breeding farms were analyzed in each category through personal interviews totalizing ten case studies. The results indicated the reasons for the adoption or rejection of a certain IT by the producers allowing for the identification of the reasons why some producers have adopted it more quickly than others. It was possible to understand the rural organization modifications due to IT adoption, for example, managerial skills improvements. In general, the processes have been improved and become easier bringing positive effects to several areas including human resources and the enterprise's image in the market.
Adoption of information technology in rural organization: The case of beef cattle breeding